Statistical competence of principles of general secondary education institutions with basic natural or mathematical or humanitarian training - Sychenko, Viktor (2020)
Statistical competence is defined as the leader’s feature of character, which characterizes his willingness and ability to organize, to process and interpret information, needed to implement management processes. Statistical competence should be considered as a substructure of functional competence of the leader as it is shown in the article. The evaluation of indicators for the basic level of statistical competence for different categories of principles of educational institutions was carried out. It is shown that for managers with humanitarian and historical and science education the probability of distortion is not less than 20%. In addition, the criterion of signs justifies the lack of effect of improving test results on the basics of mathematical and statistical literacy in the transition from a group of leaders with humanitarian, scientific and natural education. At the same time, the independence of the testing effectiveness on the basics of mathematical and statistical literacy of managers from teaching experience is shown. The obtained evaluation results and tested hypotheses indicate the need for the introduction of additional statistical education differentiated for groups of managers with mathematical education and natural sciences.